The use of loan loss provisions for capital management, earnings management and signalling by Australian banks - Asokan Anandarajan; Iftekhar Hasan; Cornelia McCarthy (Bank of Finland, 2006)
The objective of this study is to examine whether and to what extent Australian banks use loan loss provisions (LLPs) for capital management, earnings management and signalling.We examine if there were changes in the use of LLPs due to the implementation of banking regulations consistent with the Basel Accord of 1988 which made loan loss reserves no longer part of Tier I capital in the numerator of the capital adequacy ratio.We find some evidence to indicate that Australian banks use LLPs for capital management, but no evidence of a change in this behaviour after the implementation of the Basel Accord.Our results indicate that banks in Australia use LLPs to manage earnings.Further, listed commercial banks engage more aggressively in earnings management using LLPs than unlisted commercial banks.We also find that earnings management behaviour is more pronounced in the post-Basel period.Overall, we find a significant understating of LLPs in the post-Basel period relative to the pre-Basel period.This indicates that reported earnings may not reflect the true economic reality underlying those numbers.Finally, Australian banks do not appear to use LLPs for signalling future intentions of higher earnings to investors.
URN:NBN:fi:bof-20140807652
Keywords: C23; G14; M41; 330; capital management; earnings management; signalling; Australian banks